2011
DOI: 10.1111/j.1600-6143.2011.03687.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor Kidney Adapts to Body Dimensions of Recipient: No Influence of Donor Gender on Renal Function After Transplantation

Abstract: Female kidneys and kidneys from small donors have been suggested to perform worse after kidney transplantation. Here, we evaluate the impact of gender and body dimensions on posttransplantation GFR in living donor transplantation. Two hundred and ninetythree donor-recipient pairs, who were transplanted at our center were evaluated. All pairs had detailed renal function measurement ( 125 I-iothalamate and 131 Ihippuran) 4 months predonation in the donor and 2.5 months posttransplantation in donor and recipient.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In contrast, Tent et al . reported that transplanted kidneys adapt to the recipient's body size without detrimental effects on renal function and outcome based on detailed renal function measurements pre‐donation and post‐transplantation in donors and recipients. In our study we took into consideration the fact that donor and recipient weight/BSA may differ significantly by adjusting all GFR values to BSA as normalizing these values is crucial when analyzing or comparing these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tent et al . reported that transplanted kidneys adapt to the recipient's body size without detrimental effects on renal function and outcome based on detailed renal function measurements pre‐donation and post‐transplantation in donors and recipients. In our study we took into consideration the fact that donor and recipient weight/BSA may differ significantly by adjusting all GFR values to BSA as normalizing these values is crucial when analyzing or comparing these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous adult studies have shown conflicting results on the impact of using grafts from smaller donors into larger recipients in deceased and living donor kidney transplantation. [8, 14] Giral et al demonstrated from their multicenter trial that low kidney to recipient weight ratio in adult transplantation (KwRw <2.3g/kg) was an independent risk factor for post transplant graft loss by 2 years of follow up. [8] This group of patients, KwRw <2.3g/kg, also had significantly increased proteinuria at 1 year post transplant, more anti-hypertensive drug use and glomerulosclerosis compared to those with KwRw ≥2.3g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…7 The central role of increased perfusion in the early functional adaptation in humans is supported by the observed increase in renal plasma flow (RPF) after nephrectomy, of a magnitude similar to or greater than the percentage change in GFR (Table 1). 2,3,5,8 To investigate the hemodynamic mechanisms whereby GFR increases after nephrectomy, renal functional reserve capacity (RFR), defined as percentage increase in GFR after infusion of lowdose dopamine or amino acids, was evaluated in 15 LDs before donation and at a mean 6 SEM of 1.360.3 months and 4.960.8 years after donation (Table 1). 9 At both time points, the percentage increase in GFR induced by dopamine was half of that measured before donation, whereas the percentage change induced by amino acid infusion was similar before and after donation.…”
Section: Physiologic Adaptations After Uninephrectomy In Healthy Donorsmentioning
confidence: 99%
“…[2][3][4][5][6] The rapidity and reproducibility of this early increase in GFR after nephrectomy suggest a predominantly hemodynamic response.…”
Section: Physiologic Adaptations After Uninephrectomy In Healthy Donorsmentioning
confidence: 99%